Alloy digest : data on world wide materials and alloys. (ASM International, 2010)
Alloy digest is designed for use by anyone who produces, sells, buys, or uses metals, alloys, plastics, composites and ceramics in a wide range of activities such as sales, technical service, purchasing, designing, engineering, teaching, development, research, and information retrieval.